Effect of hydrogen on dislocation nucleation in alloy 718 - Stenerud, G.; Johnsen, Roy; Olsen, J.; He, J.; Barnoush, Afrooz (Elsevier Ltd, 2017)
© 2017 Hydrogen Energy Publications LLC In situ electrochemical nanoindentation has been used to study the effect of hydrogen on the nanomechanical response of Alloy 718. Observations show that hardness increase as a result of hydrogen charging. Also, the hydrogen charging gives a reduced pop-in load and pop-in width. This is related to a reduction in the energy needed for dislocation nucleation and the mobility of the dislocations in the presence of hydrogen. Two grains with different orientations has been tested here. The pop-in load and width obtained in the (101) orientation was more affected by the presence of hydrogen than those achieved in the (111) oriented grain.